(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Lime mortar is as old as human civilization. But Lime is replaced with Cement as binding material which is widely utilized today. But need for reduction in environmental pollution is turning the tide against cement. Lime with admixtures are tried in various researches nowadays. In this paper lime mortar of 1:3 ratio is with admixtures of Agricultural complex (NPKS) urea and Super phosphate in various percentages such as 1, 2, 3, 4 and 5 is studied. Commercial lime available in market was used. Red soil was used as fine aggregate. The Raw materials are tested for physical and chemical properties. Lime mortar cubes were cured in ambient temperature with moisture. The lime mortar cubes were tested for strength, water absorption and weight. Maximum strength was obtained in urea 4% and 5%.